Objetos conectados: um olhar sobre a usabilidade e design das interfaces tangíveis - Portella, Grazielle Bruscato (2016)
This research proposes a study of Tangible User Interfaces as a digital means of communication, from its conception to the moment of interaction. It poses a historical overview on the evolution of digital interfaces, from the first Graphical User Interfaces to birth of the Internet of Things, emerging phenomenon in the digital media that tangibilizes the information to connected devices. The study also investigates methods for analysis and design of Graphical Interfaces from the point of view of interaction and aesthetics. Attributes from these methods are used to propose a methodology when designing Tangible Interfaces, where its principles are combined in addition to usability and handling aspects, concepts used in Product Design methods. In order to deepen this investigation, three experimental projects from the academic field were selected to analyse the design of assorted Tangible Interfaces and apply the proposed protocol: inFORM (http://tangible.media.mit.edu/project/inform/), a multi-touch interface that addresses remote and tactile communication processes; Daily Stack (https://vimeo.com/10458491/), which works as a means by which the user arranges abstract tasks through physical blocks connected to a software; and ZeroN (http://tangible.media.mit.edu/project/zeron-levitated-interaction-element/), which explores the user-machine interaction through levitation, questioning the object as an speculative medium of interaction. As conclusions, Tangible Interfaces until need to solve some challenges such as resolution, scale and cost before we expect a complete adoption by the public. On the other hand, they can allow a richer physical interaction than Graphical User Interfaces, helping users on its manipulation without the need to have a screen present during all interactions